The peculiarities of cross-correlation between two secondary precursors – radon and magnetic field variations, induced by tectonic activity - Rusov, V.D.; Maksymchuk, V.Yu.; Ilić, R.; Pavlovych, V.M.; Bakhmutov, V.G.; Saranuk, D.N.; Vaschenko, V.M.,; Skvarč, J.; Hanžič, L.; Kosenko, S.I. (Український антарктичний журнал, 2006)
A model of precursor manifestation mechanisms, stimulated by tectonic activity and some peculiarities of observer strategy, whose main task is the effective measurement of precursors in the spatial area of their occurrence on the Earth’s daylight, are considered. In particular, the applicability of Dobrovolsky’s approximation is analyzed, when an unperturbed medium (characterized by the simple shear state) and the area of tectonic activity (local inhomogeneity caused by the change only of shear modulus) are linearly elastic, and perturbation, in particular, surface displacement is calculated as a difference of the solutions of two independent static problems of the theory of elasticity with the same boundary condition on the surface. Within the framework of this approximation a formula for the spatial distribution (of first component) of magnetic field variations caused by piezomagnetic effect in the case of perturbed regular medium, which is in simple shear state is derived. Cogent arguments in favor of linear dependence between the radon spatial distribution and conditional deformation are obtained. Changes in magnetic field strength and radon concentrations were measured along a tectonomagnetic profile of the total length of 11 km in the surroundings of the “Academician Vernadsky” Station on the Antarctic Peninsula (W 64°16´, S 65°15´). Results showed a positive correlation between the annual surface radon concentration and annual changes of magnetic field relative to a base point, and also the good coincidence with theoretical calculation.